2017
DOI: 10.1016/j.scitotenv.2017.01.099
|View full text |Cite
|
Sign up to set email alerts
|

A miniaturized bismuth-based sensor to evaluate the marine organism Styela plicata bioremediation capacity toward heavy metal polluted seawater

Abstract: Cadmium and lead are highly toxic heavy metals which cause a severe worldwide pollution. In addition to the toxic effect produced by the direct exposure, they can be bioconcentrated and accumulated in living organisms, including humans. Herein, a miniaturized and disposable electrochemical sensor was improved for the simultaneous detection of cadmium and lead ions to study the bioremediation of polluted seawater in presence of the filter-feeding marine organism Styela plicata. A screen-printed electrode modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
(33 reference statements)
0
15
0
Order By: Relevance
“…SPEs were successively treated by using the procedure reported in our previous paper [38]. Briefly, the sensor was covered by a drop of acetate buffer 50 mM + 50 mM NaCl at pH 4.6, and pre-treated by applying an oxidative potential of 1.6 V for 300 s. Subsequently, the sensor was rinsed with double-distilled water and dried at room temperature.…”
Section: Bi-ncspes Preparation and Storagementioning
confidence: 99%
See 1 more Smart Citation
“…SPEs were successively treated by using the procedure reported in our previous paper [38]. Briefly, the sensor was covered by a drop of acetate buffer 50 mM + 50 mM NaCl at pH 4.6, and pre-treated by applying an oxidative potential of 1.6 V for 300 s. Subsequently, the sensor was rinsed with double-distilled water and dried at room temperature.…”
Section: Bi-ncspes Preparation and Storagementioning
confidence: 99%
“…Each Bi-NCSPEs were obtained by in situ electroplating in the working solution, composed of 5 mL of acetate buffer 50 mM + NaCl 50 mM at pH 4.6 containing 0.5 ppm of Bi 3 + . The Bi 3 + concentration and the working solution characteristics were chosen based on investigations reported in previous studies [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]38].…”
Section: Bi-ncspes Preparation and Storagementioning
confidence: 99%
“…The vast majority of applications of electroplated Bi SPEs involve the determination of Pb, Cd, and Zn by ASV [ 16 , 17 , 19 , 26 ] but there are also selected applications of stripping analysis after adsorptive accumulation using ex situ plated BiFEs; examples of recent relevant work include the determination of Sb(III) with quercetin-5′-sulfonic acid as the chelating agent [ 69 ] and of platinum group metals (Pt, Pd, Rh) with dimethylglyoxime as the ligand [ 70 ]. Other recent notable applications include methodologies for the determination of the size and particle concentration of Cd-based quantum dots (QDs) [ 71 ], a hybrid stripping fluorescence method to detect Cd in water [ 72 ], a study of heavy metal complexation [ 73 ], and phytoremediation studies [ 74 , 75 ].…”
Section: Spes Modified With Bimentioning
confidence: 99%
“…26 Among heavy metals, cadmium (Cd) and lead (Pb) are non-essential elements with well-known toxic effects on humans. 27 Fruit water (juice) is a good source of antioxidants and inhibits the production of high ROS, while heavy metals initiate the production of such species. It could be concluded that high content of heavy metals may reduce the antioxidant property of fruits.…”
Section: Introductionmentioning
confidence: 99%